2019
DOI: 10.1002/jor.24426
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Loading Conditions on Articular Cartilage in a Metal‐on‐Cartilage Pairing

Abstract: The aim of this in vitro study was to investigate the response of articular cartilage to frictional load when sliding against a metal implant, and identify potential mechanisms of damage to articular cartilage in a metal-on-cartilage pairing. Bovine osteochondral cylinders were reciprocally slid against metal cylinders (cobalt-chromium-molybdenum alloy) with several variations of load and sliding velocity using a microtribometer. The effects of different loads and velocities, and the resulting friction coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…Among the components of SF, the protein albumin, the linear polysaccharide hyaluronic acid (HA), a mucin-like glycoprotein named lubricin, also known as proteoglycan 4 (PRG4) and surface-active phospholipids (SAPL) like 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) are the main components believed to be responsible in joint lubrication [1], [2], [4], [9]. In addition, friction depends on the properties of the contacting interface materials [10]- [12]. Necas et al (2018) found that the addition of albumin and ϒ-globulin to the lubricant reduced friction in hard-onhard pairs, but had no substantial influence on hard-on-soft pairs [13].…”
Section: Introductionmentioning
confidence: 99%
“…Among the components of SF, the protein albumin, the linear polysaccharide hyaluronic acid (HA), a mucin-like glycoprotein named lubricin, also known as proteoglycan 4 (PRG4) and surface-active phospholipids (SAPL) like 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) are the main components believed to be responsible in joint lubrication [1], [2], [4], [9]. In addition, friction depends on the properties of the contacting interface materials [10]- [12]. Necas et al (2018) found that the addition of albumin and ϒ-globulin to the lubricant reduced friction in hard-onhard pairs, but had no substantial influence on hard-on-soft pairs [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our study group reported the occurrence of biotribocorrosion in CoCr implants articulating against articular cartilage, 9 which was enhanced with frictional loading. 10 Considering the fact that CoCr ions release could be a crucial factor in progressive degeneration of articular cartilage, human osteoarthritic chondrocytes were incubated with Co (1.02-16.33 ppm) and Cr (0.42-6.66 ppm) ions at different concentrations. As metal ion levels in the joint after UKA have not been reported, CoCr ions concentrations tested were set according to the findings in MoM bearings.…”
Section: Discussionmentioning
confidence: 99%
“…Murine chondrocytes, bovine chondrocytes and cartilage explants were associated with reduced inflammatory IL-1β signalling chondrocytes after cyclic mechanical loading [58]. Osteochondral cylinders isolated from bovine stifle joints showed upregulated COL2A1 and ACAN gene expression and increased metabolic activity after high load [59].…”
Section: Common Risk Factors For Oa and Cvdmentioning
confidence: 97%